2010
DOI: 10.1111/j.1479-8301.2010.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Overview of non-pharmacological intervention for dementia and principles of brain-activating rehabilitation

Abstract: Non-pharmacological interventions for dementia are likely to have an important role in delaying disease progression and functional decline. Research into non-pharmacological interventions has focused on the differentiation of each approach and a comparison of their effects. However, Cochrane Reviews on non-pharmacological interventions have noted the paucity of evidence regarding the effects of these interventions. The essence of nonpharmacological intervention is dependent of the patients, families, and thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 58 publications
1
84
0
1
Order By: Relevance
“…For those with dementia, there is growing evidence that the cost associated with program delivery could be offset in part or full by savings related to participation benefits such as reduced medication and care needs, and falls related injuries. 30,31 Our cohort had moderate to severe dementia, which influenced their ability to follow instructions and their day to day enthusiasm to participate in exercise and/or the assessment. The motivation to adherence challenge of working with this group was demonstrated by the undulating participant attendance to sessions, even though facility staff indicated participants were enthusiastic about the program.…”
Section: Discussionmentioning
confidence: 99%
“…For those with dementia, there is growing evidence that the cost associated with program delivery could be offset in part or full by savings related to participation benefits such as reduced medication and care needs, and falls related injuries. 30,31 Our cohort had moderate to severe dementia, which influenced their ability to follow instructions and their day to day enthusiasm to participate in exercise and/or the assessment. The motivation to adherence challenge of working with this group was demonstrated by the undulating participant attendance to sessions, even though facility staff indicated participants were enthusiastic about the program.…”
Section: Discussionmentioning
confidence: 99%
“…The current findings suggest that the interactive music intervention may directly stimulate cognitive and emotional function in individuals with cognitive reserve in accordance with the previous reports of an association between the severity of BPSD and residual function due to cognitive reserve in elderly patients with severe dementia (Stern, 2009; Yamaguchi et al ., 2010). Although emotional functioning is reported to remain relatively intact until the very late stages of the disease (Ikeda et al ., 1998), aspects of cognitive dysfunction, such as reduced attention or memory impairment, could inhibit environmental recognition and reduce the ability to communicate.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that group membership plays an important role in maintaining and promoting health and well-being [4]. We proposed a new principle of rehabilitation for dementia, brain-activating rehabilitation (BAR) [5], which consists of 5 principles: (1) enjoyable and comfortable activities in an accepting atmosphere; (2) activities associated with empathetic two-way communication between staff and participant, as well as between participants; (3) praising participants to enhance motivation; (4) offering social roles to participants that enhance their remaining abilities, and (5) supportive care to prevent failure, which causes confusion of participants. In fact, BAR was conducted as a combination of several techniques (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…reminiscence therapy, reality orientation, games, physical activity, crafts, cooking, and singing) to suit the participants based on these 5 principles. BAR was expected to enhance participants’ motivation and maximize the use of their remaining functions and prevent the disuse of functions [5]. BAR was expected to enable participants to recover both a desire for life and their self-respect.…”
Section: Introductionmentioning
confidence: 99%